Participatory banking (PB) taking measures against Covid-19 in Turkey issues and proposed strategies - Hassan, Rusni; Zulfahmi, Zulfahmi (Research Center for Islamic Economics, 2021)
Not much research has been carried out to examine Participatory Bank (PB) in Turkey. This is despite the fact that Turkey has a long history in Islamic civilisation. The legacy of strong Islamic law, the majority Muslim population, and the strategic location of the country have failed to serve as a catalyst to boost the market share of participatory banking in the country. The present study aims to explore problems, solutions, and strategies for developing PBs in Turkey. This research also captures the condition of PBs in facing the Covid-19 pandemic. The study adopts a qualitative method that uses library research benefitting from various sources of literature, namely books, journals, and other sources. Semi-structured interviews were conducted with experts including practitioners, regulators, and academicians who have direct involvement in PB. The findings are presented in the form of Strength-Weakness-Opportunity-Threat (SWOT) of PBs in Turkey. Interestingly, the preliminary finding shows that the problems of PBs in Turkey stem from both internal and external factors. Lack of understanding and skills, and lack of good Shariah governance practices are the main internal factors. Lack of regulatory support, lack of public literacy, lack of academic research and educational institutions, and a regulatory system are the primary external factors. The study suggests two main solutions, namely internal and external solutions, as well as strategies to address the problems. This study could serve as a reference point for the regulator in formulating appropriate policy strategies to increase the market share of PB in Turkey.